ASIC subunit ratio and differential surface trafficking in the brain. Issue 1 (December 2016) - Wu, Junjun; Xu, Yuanyuan; Jiang, Yu-Qing; Xu, Jiangping; Hu, Youjia; Zha, Xiang-ming
Abstract Background Acid-sensing ion channels (ASICs) are key mediators of acidosis-induced responses in neurons. However, little is known about the relative abundance of different ASIC subunits in the brain. Such data are fundamental for interpreting the relative contribution of ASIC1a homomers and 1a/2 heteromers to acid signaling, and essential for designing therapeutic interventions to target these channels. We used a simple biochemical approach and semi-quantitatively determined the molar ratio of ASIC1a and 2 subunits in mouse brain. Further, we investigated differential surface trafficking of ASIC1a, ASIC2a, and ASIC2b. Results and conclusions ASIC1a subunits outnumber the sum of ASIC2a and ASIC2b. There is a region-specific variation in ASIC2a and 2b expression, with cerebellum and striatum expressing predominantly 2b and 2a, respectively. Further, we performed surface biotinylation and found that surface ASIC1a and ASIC2a ratio correlates with their total expression. In contrast, ASIC2b exhibits little surface presence in the brain. This result is consistent with increased co-localization of ASIC2b with an ER marker in 3T3 cells. Our data are the first semi-quantitative determination of relative subunit ratio of various ASICs in the brain. The differential surface trafficking of ASICs suggests that the main functional ASICs in the brain are ASIC1a homomers and 1a/2a heteromers. This finding provides important insights into the relative contribution of various ASIC complexes to acid signaling in neurons.